Mechanical and Thermal Properties of Sayong Clay/HDPE Composites - Ramli Rashidi, Ahmad; Muhammad, Arbanah; Nur Ain Sanusi, Salmi; Hajar Anaziah Muhamad, Siti; Muhammad Hafiz Shah Buddin, Meor (International Journal of Engineering and Technology, 2018)
The present study showed the effect of Sayong clay as filler on the mechanical and thermal properties of high-density polyethylene (HDPE). Different concentrations of clay (1 wt%, 3 wt% and 5 wt%) were introduced which are reinforced to HDPE composites and was prepared by melt mixing using a compounder system. The prepared composites then undergo mechanical testing and thermal study to evaluate its effectiveness after added clay. The effect of Sayong clay addition was different for each clay content and the highest tensile and flexural strength were observed for HDPE/clay composites with 5 wt% of clay at 20.98 MPa and 14.73 MPa respectively. The results showed that Sayong clay/HDPE composites with 5 wt% of clay have considerable effect upon increasing the strength properties of HDPE/clay composites. In addition, the result revealed that the accumulated clay particles that arise with addition of 3wt% of clay caused the decreased in impact strength. To study the melting point and crystallization behaviour of clay reinforced with HDPE, DSC were conducted on the samples at the temperature of 50°C to 180 °C. The result indicated that the higher the melting point of the mixture was achieved by increasing content of Sayong clay. The crystallization behaviour of HDPE is affected with the addition of Sayong clay in which make the composite easily become crystal form even at high temperature. As such, Sayong clay is can act as reinforcing filler and produced polymer composites with improved strength properties.